(untitled) (De Legibus - Law Journal, 2025)
Must the citizen be fully aware of all the legal rules before he can implement his conduct project? Wouldn’t this affect the general core of the citizen’s freedom of action? What is the best way not to unilaterally burden the citizen in the face of a project of conduct carried out in an obscure legal context derived from a regulatory deficit in the system of norms? This work aims to provide an answer to the question of the distribution of responsibility between a citizen who acts in a situation of legal uncertainty and the legal community.